Defect induced modification of structural, topographical and magnetic properties of zinc ferrite thin films by swift heavy ion irradiation - Raghavan, Lisha; Joy, P. A.; Vijaykumar, B. Varma; Ramanujan, R. V.; Anantharaman, M. R. (Nuclear Instruments & Methods In Physics Research Section B-Beam Interactions With Materials And Atoms, 2017)
Swift heavy ion irradiation provides unique ways to modify physical and chemical properties of materials. In ferrites, the magnetic properties can change significantly as a result of swift heavy ion irradiation. Zinc ferrite is an antiferromagnet with a Neel temperature of 10 K and exhibits anomalous magnetic properties in the nano regime. Ion irradiation can cause amorphisation of zinc ferrite thin films; thus the role of crystallinity on magnetic properties can be examined. The influence of surface topography in these thin films can also be studied. Zinc ferrite thin films, of thickness 320 nm, prepared by RF sputtering were irradiated with 100 MeV Ag ions. Structural characterization showed amorphisation and subsequent reduction in particle size. The change in magnetic properties due to irradiation was correlated with structural and topographical effects of ion irradiation. A rough estimation of ion track radius is done from the magnetic studies. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Spin glass; Swift heavy ion; Zinc Ferrite

Docetaxel-titanate nanotubes enhance radiosensitivity in an androgen-independent prostate cancer model - Mirjolet, C.; Martin, E.; Boudon, J.; Loiseau, A.; Chevrier, S.; Boidot, R.; Oudot, A.; Collin, B.; Joy, P. A.; Millot, N.; Créhange, G. (International Journal of Nanomedicine, 2017)
Around 40% of high-risk prostate cancer patients who undergo radiotherapy (RT) will experience biochemical failure. Chemotherapy, such as docetaxel (DTX), can enhance the efficacy of RT. Multidrug resistance mechanisms often limit drug efficacy by decreasing intracellular concentrations of drugs in tumor cells. It is, therefore, of interest to develop nanocarriers of DTX to maintain the drug inside cancer cells and thus improve treatment efficacy. The purpose of this study was to investigate the use of titanate nanotubes (TiONts) to develop a TiONts-DTX nanocarrier and to evaluate its radiosensitizing in vivo efficacy in a prostate cancer model. In vitro cytotoxic activity of TiONts-DTX was evaluated using an MTS assay. The biodistribution of TiONts-DTX was analyzed in vivo by single-photon emission computed tomography. The benefit of TiONts-DTX associated with RT was evaluated in vivo. Eight groups with seven mice in each were used to evaluate the efficacy of the nanohybrid combined with RT: control with buffer IT injection ± RT, free DXL ± RT, TiONts ± RT and TiONts-DXL ± RT. Mouse behavior, health status and tumor volume were monitored twice a week until the tumor volume reached a maximum of 2,000 mm3. More than 70% of nanohybrids were localized inside the tumor 96 h after administration. Tumor growth was significantly slowed by TiONts-DTX associated with RT, compared with free DTX in the same conditions (P=0.013). These results suggest that TiONts-DTX improved RT efficacy and might enhance local control in high-risk localized prostate cancer.
Keywords: Docetaxel Nanocarrier; nanoparticle; Prostate Cancer; Radiosensitivity; Titanate nanotubes